2019
DOI: 10.1136/gutjnl-2019-318491
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota shape ‘inflamm-ageing’ cytokines and account for age-dependent decline in DNA damage repair

Abstract: ObjectiveFailing to properly repair damaged DNA drives the ageing process. Furthermore, age-related inflammation contributes to the manifestation of ageing. Recently, we demonstrated that the efficiency of repair of diethylnitrosamine (DEN)-induced double-strand breaks (DSBs) rapidly declines with age. We therefore hypothesised that with age, the decline in DNA damage repair stems from age-related inflammation.DesignWe used DEN-induced DNA damage in mouse livers and compared the efficiency of their resolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 53 publications
0
29
0
2
Order By: Relevance
“…Furthermore, hepatocyte carcinogenesis was shown to be accelerated via enhanced genomic instability [92,93]. While impaired DNA damage response during chronic inflammation is mainly mediated by TNF α [70,94], survival and proliferation of genomic unstable hepatocytes are driven by gp130 trans-signalling by preventing p53-induced hepatocyte apoptosis (Fig. 2b) [45,93,95].…”
Section: Effect Of Il-6 On (Pre-)malignant Hepatic Cellsmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, hepatocyte carcinogenesis was shown to be accelerated via enhanced genomic instability [92,93]. While impaired DNA damage response during chronic inflammation is mainly mediated by TNF α [70,94], survival and proliferation of genomic unstable hepatocytes are driven by gp130 trans-signalling by preventing p53-induced hepatocyte apoptosis (Fig. 2b) [45,93,95].…”
Section: Effect Of Il-6 On (Pre-)malignant Hepatic Cellsmentioning
confidence: 97%
“…Obesity is linked to an increased risk of tumour development and was shown to promote HCC formation via enhanced TNF α and IL-6 secretion [69]. Alterations in the intestinal microbiota composition called "dysbiosis" are common to obesity, age-dependent inflammation [70], and chronic liver disease [71]. Venous blood that drains from the intestine first passes the liver and KCs serve as gatekeepers that protect against intestinal-derived pathogens.…”
Section: Pro-tumorigenic Roles Of Il-6/gp130mentioning
confidence: 99%
“…Aktywacja szlaku DDR w wątrobie ulegała osłabieniu już u 6-cio miesięcznych zwierząt [62]. Ponadto, sugeruje się, że związane z wiekiem zmiany w powstawaniu stanu zapalnego o niskim stopniu nasilenia oraz osłabiona odpowiedź DDR w wątrobie myszy wynikają ze zmian w mikrobiocie jelitowej tych zwierząt [63].…”
Section: Dysfunkcja Mitochondriówunclassified
“…Recently, it was demonstrated that epidermal growth factor (EGF) receptor (EGFR) signalling enhances DNA damage repair (DDR) capacity in hepatocytes [ 128 ]. Apparently, RTK signalling is linked to DDR by a so far unknown mechanism.…”
Section: Flt3 As Therapeutic Target In Leukaemiamentioning
confidence: 99%